Software Modernization Revisited: Challenges and Prospects. - Bruneliere, Hugo; Cabot, Jordi; Izquierdo, Javier Luis Canovas; Arrieta, Leire Orue-Echevarria; Strauss, Oliver; Wimmer, Manuel (Computer (00189162), 2015)
The authors discuss important factors to consider when migrating software to the cloud and offer recommendations to maximize the chance of success.